Revision of the grasshopper genus Sedulia Stål, 1878 (Acrididae: Catantopinae) from Malay Peninsula - Tan, Ming Kai; Robillard, Tony; Kamaruddin, Khairul Nizam (Zootaxa, 2016)
Southeast Asia is a highly biodiverse region with many species of grasshoppers described since the 19th century. Historical species descriptions are however often not comprehensive and do not meet the modern criteria of taxonomy. Previously used characters for identification need to be re-examined. Here, we aim to revise the taxonomy of the grasshopper genus Sedulia Stål, 1878. Using morphology and simple morphometry, we compared and investigated interspecific and intraspecific variations among the two species of Sedulia. We also redescribed both species and constructed a key to species and closely related genera.